Genetic Evaluation and Trait Association Analysis for Yield Enhancement in Soybean (Glycine max L. Merrill) - Yamini Gautam; M.K. Tripathi; Riya Mishra; Goutam Mohbe; Anurag Sharma; Sanjeev Sharma; Jagendra Singh; Lalita Bishnoi (Archives of Current Research International, 2025)
Glycine max [L.] Merrill is an internationally significant leguminous crop, appreciated for its high protein ( 40%) and oil ( 20%) content. Enhancing seed yield, a polygenic trait influenced by multiple agronomic characters, remains a major breeding objective. Present investigation was conducted during Kharif, 2024 at the Research Farm, Zonal Agricultural Research Station, Morena, RVSKVV, Gwalior, M. P., India, using 60 genetically diverse genotypes laid out in a Randomized Block Design with two replications. Substantial genetic variability was observed for main yield attributing traits. Phenotypic coefficients of variation (PCV) exceeded genotypic coefficients (GCV), indicating environmental influence; however, small PCV-GCV differences for many traits suggested existence of a strong genetic basis. High heritability (>99%) and genetic advance as percentage of mean (GAM) were investigated for numbers of seeds per plant, biological and seed yield per plant signified that traits governed largely by additive gene action. Correlation analysis revealed significant positive associations of seed yield with numbers of seeds and pods per plant, biological yield, harvest index and hundred-seed weight. Path coefficient analysis identified biological yield as having the highest direct positive effect on seed yield, tracked by harvest index and numbers of seeds per plant. Whereas, negative direct effects of some traits were offset by strong indirect contributions via key yield contributing components. These findings highlighted that traits of high breeding value, offering essential guidance for selection indices in soybean improvement. Integrating these findings with molecular tools could accelerate the development of high-yielding, climate-resilient cultivars suitable to diverse agro-ecological zones.